A survey of methods of text-to-image translation - Pydorenko, D. O. (ХНУРЕ, 2019)
The given work is devoted to the text-to-image translation. This translation can be realized in two steps. First, a large text should be transformed into a small set of captions. Second, these captions should be used to generate images. There are different methods that can help to implement both steps.